2020
DOI: 10.2147/rru.s242398
|View full text |Cite
|
Sign up to set email alerts
|

<p>Review of Testicular Tumor: Diagnostic Approach and Management Outcome in Africa</p>

Abstract: Testicular cancer is a common malignancy in young males with higher incidence in developed nations but with the lowest incidence in Africa (0.3-0.6/100 000). Ironically, the global testicular cancer mortality rate has shown a reverse trend to its incidence with higher rates in low-and middle-income countries (0.5 per 100 000) than in high-income countries. Data from GLOBOCAN 2008 have shown relatively high mortality rates in sub-Saharan countries like Mali, Ethiopia, Niger and Malawi. The prognosis of testicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 21 publications
(125 reference statements)
1
33
0
Order By: Relevance
“…In Africa, the lack of diagnostic tool, poor health seeking behavior and poverty have been a barrier to both diagnosis and treatment of UCs [ 23 ]. Contemporary reviews from Sub-Saharan Africa have revealed much later stages of presentation of other rare genitourinary cancers including penile and testicular tumor [ 24 , 25 ]. To date, the available literature on UC of the upper tract or urethra remains sparse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Africa, the lack of diagnostic tool, poor health seeking behavior and poverty have been a barrier to both diagnosis and treatment of UCs [ 23 ]. Contemporary reviews from Sub-Saharan Africa have revealed much later stages of presentation of other rare genitourinary cancers including penile and testicular tumor [ 24 , 25 ]. To date, the available literature on UC of the upper tract or urethra remains sparse.…”
Section: Discussionmentioning
confidence: 99%
“…World J Oncol. 2021;12(1): [20][21][22][23][24][25][26][27] and excision of the bladder cuff because of a considerable risk of tumor recurrence in this area. There is strong evidence to suggest that adjuvant instillation of mitomycin within 72 h of surgery can reduce the recurrence rate within the first year [2,9,10].…”
Section: Rare Urogenital Cancersmentioning
confidence: 99%
“…As in other non-seminomatous tumors, the treatment of embryonal carcinoma is based primarily on the chemotherapy [6] but typical treatment for a suspicious testicle mass is orchiectomy. Considering that embryonal carcinoma is resistant to radiation, treatment protocol consists of orchiectomy and chemotherapy [5,9]. Our patient received surgical treatment with left high radical orchiectomy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, early diagnosis and treatment of embryonal carcinoma cases are very important [3]. As in many testicular tumors, embryonal carcinoma is also detected by the patient or coincidentally in examination in form of pain-free or (less frequently) painful palpable mass [5][6][7][8][9][10]. When pain or mass is detected in testis, the first imaging method to be used is USG.…”
Section: Introductionmentioning
confidence: 99%
“…
Testicular tumour is the most malignant cancer in young males 15 to 34 years of age. Its accounts for 1% of all male cancer and 5% of urological malignancy [1]. The management of this type of cancer is radical inguinal orchiectomy which is the gold standard for the diagnosis and initial management of a suspected testicular cancer.
…”
mentioning
confidence: 99%